Not only scholarships : The Ford Foundation, its material support, and the rise of social research in Poland - Kilias, Jarosław (Serendipities. Journal for the Sociology and History of the Social Sciences, 2021)
This paper deals with the Ford Foundation’s support for sociology in Poland, especially with its influence on the development of the social research in this country. It is based on materials from both American and local archives—sources which have never before been combined. The role of the Ford scholarships for Polish scholars is relatively well known, but this paper covers two less known aspects of the Foundation’s activity—funding American sociologists’ visits to Poland and the material support for local libraries and statistical laboratories. The American visitors were neither numerous, nor was their role particularly significant, except one: Herbert Menzel, who spent almost a year in Poland, helping to spread the know-how of quantitative social research. The Ford Foundation also supported libraries and helped to equip the statistical research lab of the Institute of Sociology of the Polish Academy of Science, tripling the technical base of quantitative social research in this country. Although Polish empirical sociology was successful and Poland became the center of empirical research in Eastern Europe for a while, Poles were hardly able to spread it all over the region on their own, as they were dependent on Western support.